A Bibliometric Review of Accounting Profession - Loso Judijanto (Westscience Press, 2026)
This bibliometric review explores the evolving landscape of accounting research by analyzing scholarly articles and their citation patterns over the past two decades. Using bibliometric tools such as citation analysis, co-authorship networks, and keyword co-occurrence analysis, this study identifies key research themes and trends in the field of accounting. The analysis highlights the continued dominance of traditional topics such as auditing, financial reporting, and corporate governance, while also unveiling the rapid emergence of new areas like artificial intelligence, data analytics, and sustainability accounting. This paper further emphasizes the growing integration of technology and global challenges into accounting research, reflecting the profession’s adaptation to the digital age. The findings provide valuable insights for both academics and practitioners, offering a comprehensive view of the current state of accounting research and suggesting directions for future studies.